The Influence of Financial Literacy and Transparency on Budget Management in the Vote Counting Committee - Salsabila; Totanan, Chalarce; Parwati, Ni Made Suwitri; Pakawaru, Muhammad Ilham (GoAcademica Research & Publishing, 2025)
The current research examines the impact regarding financial literacy and transparency on budget management within Voting Organizing Committees (PPS) in Donggala Regency, Indonesia. A quantitative approach is employed, involving a census of 501 PPS members from 167 subdistricts. Data is gathered via structured surveys and assessed using multiple linear regression in SPSS software. The analysis includes instrument validation, reliability testing, and classical assumption diagnostics such as normality, multicollinearity, and heteroscedasticity tests. Hypothesis testing is conducted through t-tests and F-tests, with model explanatory power assessed using the coefficient of determination (r2). The findings reveal that financial literacy and transparency both significantly enhance budget management, accounting for 78.1% of the model’s explanatory power. Specifically, increased financial literacy enables PPS members to plan, allocate, and report budget usage effectively, while transparency enhances accountability and deters misuse through open financial disclosures. The study’s implications are twofold: theoretically, it supports Public Financial Management and Agency theories, highlighting the importance of competence and openness in public budget administration; practically, it calls for integrated training programs to enhance financial skills and transparency in electoral governance. These results contribute to improving democratic integrity and public trust in electoral processes.